Methodologies for the Crisis states in the Czech Republic - Šustr, Martin; Pluhař, Matěj; Soušek, Radovan; Fuchs, Pavel; Nedeliaková, Eva (International Institute of Informatics and Systemics, 2016)
All human activities are realized with certain risk. However the crisis occasionally occurs. After crisis situation is necessary to confront with the coordinated approach. For coordination of aproachech is suitable Methodologies for crisis situation.
Použití metodik pro řešení krizových stavů v České republice
Keywords: railway transport; crisis situation; threat; methodologies; law regulation; železniční doprava; krizová situace; hrozba; metodika; právní regulace